Fluorescence lifetime tuning--a novel approach to study flip-flop kinetics in supported phospholipid bilayers - Kułakowska, Anna; Jurkiewicz, Piotr; Sýkora, Jan; Benda, Ales; Mely, Yves; Hof, Martin (Journal of fluorescence, 2010)
In the present work we introduce a straightforward fluorescent assay that can be applied in studies of the transbilayer movement (flip-flop) of fluorescent lipid analogues across supported phospholipid bilayers (SPBs). The assay is based on the distance dependent fluorescence quenching by light absorbing surfaces. Applied to SPBs this effect leads to strong differences in fluorescence lifetimes when the dye moves from the outer lipid leaflet to the leaflet in contact with the support. Herein, we present the basic principles of this novel approach, and comment on its advantages over the commonly used methods for investigating flip-flop dynamics across lipid bilayers. We test the assay on the fluorescent lipid analog Atto633-DOPE and the 3-hydroxyflavone F2N12S probe in SPBs composed of DOPC/ DOPS lipids. Moreover, we compare and discuss the flip-flop rates of the probes with respect to their lateral diffusion coefficients.
Keywords: fluorescence; Lipid Bilayers; Fluorescent Dyes; Kinetics; lipidové dvojvrstvy; Time Factors; časové faktory; fosfolipidy; chemické techniky analytické; fosfatidylcholiny; difuze; fosfatidylseriny; fluorescenční barviva; Phosphatidylcholines; fosfatidylethanolaminy; Phospholipids; Phosphatidylserines; Phosphatidylethanolamines; Diffusion; Fluorescence; kinetika; Chemistry Techniques, Analytical